An atomistic perspective on lithiation-induced stress in silicon nanopillars. (15th July 2018) - Fan, Feifei; Yang, Hui; Zeng, Zhi
Abstract: We present reactive force field simulations that provide an atomistic understanding of lithiation-induced stress generation in silicon nanopillars. We investigate two-phase lithiation by developing a new protocol for simulation of formation and movement of an atomically sharp phase boundary. This protocol involves the layer-by-layer insertion of lithium atoms in the silicon lattice. The simulation results show the development of compressive stresses at the phase boundary and hoop tension near the surface of a Si nanopillar, thereby highlighting the atomistic underpinning of lithiation-induced stress. The work enables a direct mapping between atomistic and continuum modeling of lithiation-induced stress in large-volume-change electrodes. Graphical abstract: Unlabelled Image